New autonomous scheme of iterative learning control for online implementation. (2018) - Noueili, Leila; Chagra, Wassila; Lahmari, Moufida Ksouri
The purpose of this paper is to achieve the implementation of a new autonomous control scheme combining two phases: online error learning and control procedure implementation on the Arduino-Uno microcontroller. This paper presents the realisation of a real time implementation of three control algorithms applied to a resistor-capacitor (RC) circuit. Two iterative learning control schemes, proportional iterative learning control (ILC-1) and optimal iterative learning control (ILC-2) are studied and implemented and their performance results are also compared to proportional-integrator (PI) controller. The experimental results show the feasibility and the efficiency of the online autonomous control scheme.